2011
DOI: 10.1016/j.amepre.2011.06.046
|View full text |Cite
|
Sign up to set email alerts
|

Use of Global Positioning Systems to Study Physical Activity and the Environment

Abstract: Context-The Global Positioning System (GPS) represents an innovative way to objectively assess the spatial locations of physical activity behavior.Purpose-The aim of this systematic review was to determine the capability of GPS to collect high quality data on the location of activities in research on the relationship between physical activity and the environment.Evidence acquisition-Published and unpublished articles identified from seven electronic databases, reference lists, bibliographies and websites up to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
188
1
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(197 citation statements)
references
References 33 publications
2
188
1
3
Order By: Relevance
“…An assessment of study quality allows the reader to examine results stratified by their quality and their effects. Though many literature reviews about built environments and physical activity have used the label 'systematic review' [11-15, 27, 29-31, 42-46], few assessed the quality of the primary studies [12,15,38,43]. Tools for the assessment of the quality and validity of intervention studies have been suggested [41].…”
Section: Strength Of Evidencementioning
confidence: 99%
See 2 more Smart Citations
“…An assessment of study quality allows the reader to examine results stratified by their quality and their effects. Though many literature reviews about built environments and physical activity have used the label 'systematic review' [11-15, 27, 29-31, 42-46], few assessed the quality of the primary studies [12,15,38,43]. Tools for the assessment of the quality and validity of intervention studies have been suggested [41].…”
Section: Strength Of Evidencementioning
confidence: 99%
“…Therefore, another criterion in guidelines for systematic reviews is that authors of literature reviews should search for grey literature [33,41,55]. However, with few exceptions [14,15,38,56,57], reviews on environments and physical activity only included articles from peer-reviewed journals. Sources of grey literature could be found through databases such as PsycEXTRA (http://www.apa.org/psycextra), Open Grey (http://www.…”
Section: Publication Biasmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the emergence of GPS and GPS-enabled instruments creates the ability to systematically collect characteristics of the built and social environments at fine-spatial scales not previously accessible to researchers. Though a number of studies have employed GPS and GPS-enabled technologies in health investigations, [21][22][23] our study is focused solely on their use in understanding AST and child injury surveillance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…GPS has been used in health research to gain information on issues such as pollutant exposure (by tracking how participants move through neighborhoods), 13 management of exercise 14 and monitoring of chronic conditions. 15 Smartphone-based geosocial networking applications, which allow users to connect with others based on proximity, have facilitated targeted geographic recruitment of research participants.…”
Section: Mobile Technologies That Allow Measurement Of Social Networkmentioning
confidence: 99%